HJ11 decoction restrains development of myocardial ischemia-reperfusion injury in rats by suppressing ACSL4-mediated ferroptosis - Zhang, Fangyuan; Li, Ziyun; Gao, Ping; Zou, Jiaxi; Cui, Yuting; Qian, Yi; Gu, Renjun; Xu, Weiming; Hu, Jingqing (Frontiers in Pharmacology, 2022)
HJ11 is a novel traditional Chinese medicine, developed from appropriate addition and reduction of Simiaoyongan decoction, which has been commonly used to treat ischemia/reperfusion (I/R) in clinic. However, the mechanism of action involved is still unclear. It has been revealed that ferroptosis is a critical factor to promote the myocardial I/R injury, pathogenic ferroptosis mediated lipid peroxidation was demonstrated to cause I/R. Therefore, this paper explored whether HJ11 ameliorates the myocardial I/R injury by attenuating the ferroptosis.We explored the effect of ACSL4 expression on iron death by preparing a rat model of myocardial ischemia-reperfusion and OGD/R-induced H9c2 cells. It was discovered that HJ11 decoction improved the cardiac function, attenuated the injury, apoptosis, oxidative stress, mitochondrial damage and iron accumulation, and reduced infarct size in the myocardial I/R rats. Meanwhile, HJ11 decoction suppressed the expression of ferroptosis-promoting proteins (Acyl-CoA synthetase long-chain family member 4, ACSL4 and Cyclooxygenase-2, COX2) but promoted the expression of ferroptosis-inhibiting proteins (Ferritin heavy chain 1, FTH1and Glutathione-dependent lipid hydroperoxidase glutathione peroxidase 4, GPX4) in the myocardial tissues of myocardial I/R rats. Similar results were found the in the oxygen glucose deprivation/reperfusion (OGD/R)-induced H9c2 cells. Interestingly, ACSL4 knockdown attenuated the iron accumulation, oxidative stress and ferroptosis in the OGD/R-treated H9c2 cells. However, ACSL4 overexpression counteracted the inhibition of HJ11 decoction on the OGD/R-triggered oxidative stress and ferroptosis in H9c2 cells. These findings revealed that the potential molecular mechanism by which HJ11 decoction restrains development of myocardial I/R via the regulation of ACSL4-mediated ferroptosis, indicating that HJ11 may be an effective medication to treat myocardial I/R.